P268 Introduction of the low risk ankle rule to a paediatric emergency department: a quality improvement initiative. (June 2019) - Tormey, Peter; Callender, Orla; McNamara, Roisin; Okafor, Ike; Fitzpatrick, Patrick; Kandamany, Nandini; McCrudden, Tracey
Abstract : Introduction: Ankle injuries are common in children (∼ 2% of presentations to PEDs) 1 X-rays are ordered for 85–95% of patients but only 12% of x-rays reveal a fracture. 1 Clinical prediction rules such as The Low Risk Ankle Rule (LRAR) exist to help clinicians safely reduce the frequency of radiography in these injuries. The LRAR has been shown to reduce imaging by up to 60% without missing any clinically signficant fractures. 1 Aim: To introduce the LRAR to our department and study its effect on our rate of radiography and length of stay (LOS). We also sought to identify complications related to its use, such as missed fractures and representations. Methods: A baseline audit was performed to determine our baseline rate of radiography. The implementation strategy involved: staff education sessions, distribution of study information and visual reminders throughout the department, introduction of mandatory prompts into the x-ray ordering system and a 3 week pilot period. Results: The baseline ankle x-ray rate was 879/969 (90.7%). This reduced to 40/92 (43.4%) using the LRAR, a reduction of 47.3%. The average LOS decreased from 132 minutes before the implementation to 123 minutes after. There were no re-presentations with missed fractures. Further 12 month follow up data after the initial implementation period showed a persistent 46% reduction in the frequency of ankle x-rays performed, compared with the baseline data. Conclusions: The LRAR has been shown to safely reduce the frequency of radiography in ankle injuries. 1, 2, Other studies have demonstrated a reduction in x-ray frequency of 22–60%. 1, 2, Our study was in keeping with these previous studies, while also not missing any fractures, further supporting the use of The LRAR in paediatric emergency departments. The LRAR continues to be used effectively in our department. Follow on data showed an annual saving of €28, 247. References: Boutis, K., Von Keyserlingk, C., Willan, A., Narayanan, U. G., Brison, R., Grootendorst, P., … Goeree, R. (2015). Cost Consequence Analysis of Implementing the Low Risk Ankle Rule in Emergency Departments. Annals of Emergency Medicine, 66, 455–463.e4. Boutis, K., Komar, L., Jaramillo, D., Babyn, P., Alman, B., Snyder, B., … Schuh, S. (2001). Sensitivity of a clinical examination to predict need for radiography in children with ankle injuries: a prospective study. The Lancet, 358 (9299), 2118–2121